Porous Si-based nanosystems for immunotherapy applications - Li, Jiachen; Carvalho, Gabriela Corrêa [UNESP]; Chorilli, Marlus [UNESP]; Santos, Hélder A. (Springer Nature, 2024)
After decades of research, immunotherapy has been explored in many disease treatments, such as antivirus, antibacterial, and anticancer treatments. For example, porous Si-based nanoparticles, being biocompatible and biodegradable biomaterials, have been studied and investigated extensively in various biomedical fields, including cancer immunotherapy. In this chapter, we introduce the typical immunotherapy research based on the two types of porous Si, porous silicon and porous silica nanoparticles. We highlight the fabrication procedures of these nanosystems and their therapeutic applications, and we also discuss how the porous Si-based nanoparticles can significantly improve the effect in cancer immunotherapeutic applications.
Keywords: Cancer; Immune response; Immunotherapy; Nanoparticles; Porous silicon